Enamel crystals of mice susceptible or resistant to dental fluorosis: an AFM study - Marília Afonso Rabelo BUZALAF; Carolina Silveira BARBOSA; Aline de Lima LEITE; Sywe-Ren CHANG; Jun LIU; Agata CZAJKA-JAKUBOWSKA; Brian CLARKSON (University of São Paulo, 2014)
Objective: This study aimed to assess the overall apatite crystals profile in the enamel matrix of mice susceptible (A/J strain) or resistant (129P3/J strain) to dental fluorosis through analyses by atomic force microscopy (AFM). Material and Methods: Samples from the enamel matrix in the early stages of secretion and maturation were obtained from the incisors of mice from both strains. All detectable traces of matrix protein were removed from the samples by a sequential extraction procedure. The purified crystals (n=13 per strain) were analyzed qualitatively in the AFM. Surface roughness profile (Ra) was measured. Results: The mean (±SD) Ra of the crystals of A/J strain (0.58±0.15 nm) was lower than the one found for the 129P3/J strain (0.66±0.21 nm) but the difference did not reach statistical significance (t=1.187, p=0.247). Crystals of the 129P3/J strain (70.42±6.79 nm) were found to be significantly narrower (t=4.013, p=0.0013) than the same parameter measured for the A/J strain (90.42±15.86 nm). Conclusion: enamel crystals of the 129P3/J strain are narrower, which is indicative of slower crystal growth and could interfere in the occurrence of dental fluorosis.